2014
DOI: 10.1039/c4cp00566j
|View full text |Cite
|
Sign up to set email alerts
|

Innovative statistical interpretation of Shewanella oneidensis microbial fuel cells data

Abstract: The last decade of research has made significant strides toward practical applications of Microbial Fuel Cells (MFCs); however, design improvements and operational optimization cannot be realized without equally considering engineering designs and biological interfacial reactions. In this study, the main factors contributing to MFCs' overall performance and their influence on MFC reproducibility are discussed. Two statistical approaches were used to create a map of MFC components and their expanded uncertainti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The applied statistical interpretation of the results from a significant amount of MFCs data showed that design parameters were the dominating factors when the necessity bacterial biofilm was developed. The same conclusion was made when the expanded uncertainties of the main operational characteristics were evaluated (Figure 3) [28]. a.…”
Section: Multi-parameter Approach: Identify and Isolate The Factors Hmentioning
confidence: 60%
See 1 more Smart Citation
“…The applied statistical interpretation of the results from a significant amount of MFCs data showed that design parameters were the dominating factors when the necessity bacterial biofilm was developed. The same conclusion was made when the expanded uncertainties of the main operational characteristics were evaluated (Figure 3) [28]. a.…”
Section: Multi-parameter Approach: Identify and Isolate The Factors Hmentioning
confidence: 60%
“…Through evaluation of the expanded uncertainty of microbial fuel cells, the variations in electrodes resistance and mostly difference in their electrochemical accessible surface area were identified as the main parameters causing irreproducibility of MFCs responses [24,25]. The idea of using statistical approaches for analysis of biofuel cells was further enlarged to include Design of Experiments, Principal Component Analysis (PCA) and Canonical Correspondence Analysis [7,[26][27][28][29]. The applied statistical interpretation of the results from a significant amount of MFCs data showed that design parameters were the dominating factors when the necessity bacterial biofilm was developed.…”
Section: Multi-parameter Approach: Identify and Isolate The Factors Hmentioning
confidence: 99%
“…A statistical analysis using PCA/UMR approach was conducted for a Shewanella oneidensis MFC to discern the relative importance of various factor on MFC performance [101]. Buffer pH is a main parameter determining MFC performance.…”
Section: Electrode Materialsmentioning
confidence: 99%
“…[22]. The inability to distinguish the influence of only one parameter from the whole set of parameters that are usually altered through the commonly used surface modification techniques is a result of the intercorrelation between the introduced variances in the parameters’ magnitudes [23]. Therefore, the impact of the anode surface chemistry on current and power output in MFC should be studied using flat electrode material, thus de-coupling chemical effects from change in surface morphology.…”
Section: Introductionmentioning
confidence: 99%